Occurrence of hypothyroidism and its correlation with reproductive health problems: a cross sectional study - Kumar, Selvi; Kotur, Pushpa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Thyroid dysfunction is 10 times more common in women than in men. Hypothyroidism among women of reproductive age group is linked to menstrual irregularities, polycystic ovarian syndrome (PCOS), miscarriage and infertility. Several studies are available in the literature reporting regarding impact of hypothyroidism on one or the other isolated problems of reproductive health problems. Methods: This cross-sectional study is conducted including 290 participants having various reproductive health problems attending the gynaecology OPD of a rural based tertiary care hospital of Tamil Nadu during the year 2017-2018.These participants were investigated for thyroid dysfunction and its correlation of hypothyroidism with reproductive health problems viz. menstrual irregularities, Polycystic ovarian diseases (PCOS), infertility and pregnancy loss was studied. Results: It was observed that 80.6% of the 290 participants were euthyroid and 16.97% were hypothyroid, who presented with menstrual irregularities like menorrhagia (28.6%), oligomenorrhea (20.8%), amenorrhoea (21.3%), PCOS (28.6%), infertility (21.6%) and 23.8% hypothyroid women had pregnancy losses of varying number. Conclusions: In present study the occurrence of hypothyroidism was found to be 16.89%. Since hypothyroidism has close association with problems like menstrual irregularities, PCOS, miscarriages and infertility, thyroid function test should be routinely recommended for these women. Thyroid dysfunction can be corrected with simple, cost-effective treatment. This will help in improvement in pregnancy outcome and also avoid subjecting women for major surgeries for menorrhagia.